Nonsense mutations in the alcohol dehydrogenase gene of Drosophila melanogaster correlate with an abnormal 3' end processing of the corresponding pre-mRNA. - Brogna, S. (RNA (New York, N.Y.), 1999)
From bacteria to mammals, mutations that generate premature termination codons have been shown to result in the reduction in the abundance of the corresponding mRNA. In mammalian cells, more often than not, the reduction happens while the RNA is still associated with the nucleus. Here, it is reported that mutations in the alcohol dehydrogenase gene (Adh) of Drosophila melanogaster that generate premature termination codons lead to reduced levels of cytoplasmic and nuclear mRNA. Unexpectedly, it has been found that the poly(A) tails of Adh mRNAs and pre-mRNAs that carry a premature termination codon are longer than in the wild-type transcript. The more 5' terminal the mutation is, the longer is the poly(A) tail of the transcript. These findings suggest that the integrity of the coding region may be required for accurate mRNA 3' end processing.